Urban proximity, conflict, and agricultural development: Evidence from Myanmar - Steinhübel, Linda; Minten, Bart (International Food Policy Research Institute, 2023)
Urbanization and violent conflict have been two global trends gaining more and more momentum in recent years. This has important implications for agricultural development, which unfortunately are still not well understood. Urban proximity is generally associated with agricultural intensification and improved market participation, while farming systems in remote areas are characterized by larger shares of subsistence production. Such differences along the remoteness gradient likely also play a role in how conflict exposure affects agricultural production. That is, we must assume that the effect of conflict on agricultural development is location-dependent—a fact that is generally neglected in empirical analysis. We address this gap by drawing from a unique nationally representative data set of 2,292 paddy farmers in Myanmar and estimating the effect of conflict exposure and travel times on agricultural production during the monsoon season of 2021. By applying multivariate additive models, we allow for nonlinear and interacted effects of conflict exposure and urban proximity, thereby explicitly exploring spatial variation in the effect of conflict exposure. We find strong positive effects of urban proximity on paddy rice intensification and sales, while conflict exposure has disproportionately negative effects in direct proximity to urban centers and very remote areas. For agricultural development—and smallholder incomes in general—this means that productive areas, on the one hand, and the poorest areas of the country, on the other hand, are especially affected by conflict.